2021
DOI: 10.1108/jhti-10-2020-0205
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging customer-to-customer interactions to create immersive and memorable theme park experiences

Abstract: PurposeTheme park experiences ubiquitously unfold in the presence of others. In acknowledgement of this important part of theme park consumption, this research set out to examine if other visitors help create an immersive environment and, in turn, memorable experiences for theme park visitors.Design/methodology/approachAn online survey was distributed to 561 theme park visitors. Structural equation modeling (AMOS 26) was used for testing the hypotheses in the proposed framework.FindingsResults of SEM analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 65 publications
2
22
0
Order By: Relevance
“…Although there is variation in the division of the dimensions of MTEs, there is agreement regarding what constitutes an unforgettable tourism experience (de Freitas Coelho and de Sevilha Gosling, 2018 ). Antecedent variables that affect MTEs include tourists' psychological factors, such as perceived similarity (Wei et al, 2021 ), and destination level factors, such as destination attributes or services (Kim, 2014 ). Outcome variables of MTEs include loyalty, RI (Coudounaris and Sthapit, 2017 ; Chen and Rahman, 2018 ; Wong and Lai, 2021 ), subjective well-being (Sthapit and Coudounaris, 2018 ), and PA (Vada et al, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there is variation in the division of the dimensions of MTEs, there is agreement regarding what constitutes an unforgettable tourism experience (de Freitas Coelho and de Sevilha Gosling, 2018 ). Antecedent variables that affect MTEs include tourists' psychological factors, such as perceived similarity (Wei et al, 2021 ), and destination level factors, such as destination attributes or services (Kim, 2014 ). Outcome variables of MTEs include loyalty, RI (Coudounaris and Sthapit, 2017 ; Chen and Rahman, 2018 ; Wong and Lai, 2021 ), subjective well-being (Sthapit and Coudounaris, 2018 ), and PA (Vada et al, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to this, amusement theme experience interactions between friends and family may be more attractive to visitors than heritage theme parks [31]. Moreover, as many of the newest amusement theme parks have adopted information and communication technology (e.g., VR) devices to further attract visitors, visitors' willingness to travel is enhanced [17]. Based on previous considerations and inspirations, the present study focuses on amusement theme park destinations.…”
Section: Theme Parks In Tourismmentioning
confidence: 99%
“…Cognitive dimension refers to the evaluation of destination features, and may be related to weather, transportation, recreational facilities, attitudes, food, landscape, and destination locals, while the affective dimension refers to visitors' feelings or emotional reactions to the destination, more at the psychological level [1]. Numerous studies have demonstrated the relationship between cognitive image and affective image, and cognitive image positively influences affective image in tourism experience [17,39,40]. Based on previous literature, we propose the following hypothesis.…”
Section: Destination Imagementioning
confidence: 99%
See 1 more Smart Citation
“…This bond can motivate travel and enhance tourists' heritage experiences (Lochrie et al , 2019). However, memorable tourism experiences (MTEs) are not solely reliant on pre-experience motivations, but are instead also influenced by visitors' perceptions of multiple on-site stimuli (Buehring et al , 2019) and customer-to-customer interactions (Wei et al , 2021). Within heritage contexts, this is typically contingent on how authentic site offerings and objects therein are perceived to be, alongside the aggregated experiential aspects of a destination (Kolar and Zabkar, 2010).…”
Section: Introductionmentioning
confidence: 99%